Atuação do Médico Veterinário na Área Comercial: Avanço do Mercado de Cuidados Pet. - Sousa, Débora Santana de (Universidade Federal do Tocantins, 2023)
The supervised curricular internship was conducted under the supervision of Veterinary Doctor Crispim Anderson Rodrigues Correia, representative and sales promoter of the company BIRIVET COMÉRCIO DE PRODUTOS VETERINÁRIOS LTDA (Agro Veterinária Suzuki), located in the city of Araguaína-TO, and under the guidance of Prof. Drª. Katyane de Sousa Almeida. The internship took place from August 3 to November 30, 2020, totaling a workload of 704 hours. Activities were carried out in the areas of commercialization, product promotion, veterinary technical guidance, training for clerks and veterinarians, telemarketing assistance and clinical case monitoring of a two-year-old pinscher dog, with chronic dermatitis and leishmaniasis diagnosis, with dermatological products that the company represents for their future promotion, and data collection to analyze the increase in sales of dermatological products during the last years, proving not only the great numerical advance in the area, but also the importance, the valorization and concern that the people are giving more and more to small animals.